BUDAYA MERANTAU PEREMPUAN MINANGKABAU (Studi Kasus Perantau Perempuan Minangkabau di Kota Pekanbaru) - Dwi Putri Rahmalia; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
At this time, in the millineal era, the development of Information and Technology Science and the increasing emancipation of women that affect social change in Minangkabau society, for example changes in values, behavior patterns, and other habits. One of them is migrating that has undergone a change, both in terms of patterns and values in it. Wandering at this time is not only done by men but many Minangkabau women also migrate. The focus topic of this research is "Culture of Moving Minangkabau Women (Case Study Migrating Minangkabau Women in Pekanbaru City)", the issues raised in this study are: What is the background of Minangkabau women migrating? and What are the Minangkabau women getting while migrating in Pekanbaru? The purpose of this research is to find out the background of Minangkabau women migrating and to find out what Minangkabau women have gained while migrating. The research method used is a qualitative research method. Research location in Pekanbaru city. As for the informants in this study were 9 people according to predetermined criteria (purposive sampling).. Data collection techniques used are observation, interviews and documentation, the results of research in general are the reasons for Minangkabau women to migrate because of economic factors that are difficult to accommodate, supporting social factors and also conflicting customs. And there are changes in the standard of living for Minangkabau women who migrate, starting in terms of economic, social and well-being. Keywords: Minang Women, Merantau.